Financial profile 2008 (Asian Development Bank (ADB), 2008)
The Asian Development Bank promotes the economic growth and social development of its developing member countries by means of a wide range of activities and initiatives. ADB's annual financial profile provides the facts and figures behind ADB's lending activities and describes ADB as a borrower.